Factors related to irritable bowel syndrome and differences among subtypes: A cross-sectional study in the UK Biobank - Wang, Kexin; Liu, Huan; Liu, Jingjing; Han, Liyuan; Kang, Zheng; Liang, Libo; Jiang, Shengchao; Meng, Nan; Chen, Peiwen; Xu, Qiao; Wu, Qunhong; Hao, Yanhua (Frontiers in Pharmacology, 2022)
Background Irritable bowel syndrome (IBS) reduces patients’ quality of life and causes great burdens due to its unclear pathogenesis and criteria for diagnosis. This study aimed to explore the differences in prevalence and the influencing factors for IBS and its subtypes. Methods The UK Biobank surveyed 174,771 adult participants who completed the digestive health questionnaire (DHQ) through emails and websites. DHQ included the Rome III criteria, the IBS symptom severity score and the Patient Health Questionnaire 12 Somatic Symptom score. The UK Biobank also asked regarding previous IBS diagnosis, diagnosis for post-infectious IBS (PI-IBS), and environmental exposures and associated conditions (including anxiety or depression, based on treatment sought or offered). Pearson's Chi-squared test or Wilcoxon's rank-sum test was used for potential associations. Binary logic regression based on sex stratification was used to examine associations between selected factors and IBS and its subtypes. Results This study included 31,918 participants who met the Rome III criteria for IBS. The pooled prevalence of IBS in UK Biobank was 18.3%, with mixed IBS as the predominant subtype (59.0%), followed by diarrhoea-predominant IBS (25.1%), constipation-predominant IBS (14.7%) and untyped IBS (1.1%). IBS was significantly associated with somatisation [males: OR = 5.326, 95% CI = 4.863-5.832; females: OR = 4.738, 95% CI = 4.498-4.992] and coeliac disease [males: OR = 4.107, 95% CI = 3.132-5.385; females: OR = 3.783, 95% CI = 3.310-4.323]. Differences in antibiotics and mental status were presented among subtypes and sex. Furthermore, 1,787 individuals were diagnosed with PI-IBS in the group of patients with IBS. The prevalence of PI-IBS in IBS was 16.6% in the UK Biobank, and it was characterized by diarrhoea, fever, bloody diarrhoea, and vomiting. Conclusions Somatisation and coeliac disease are primary risk factors for IBS. Distinguishing differential risk factors are critical for the precise diagnosis and treatment of IBS subtypes, particularly sex-specific differences in mental health status. General practitioners should focus on the treatment according to IBS subtypes.